The impact of perceived control and power on adolescents’ acceptance intention of intelligent online services - Yan, Ying; Fan, Wenfang; Shao, Bingjia; Lei, Yuanyang (Frontiers in Psychology, 2022)
A higher level of intelligence can improve adolescents’ interactions with intelligent online services, although overemphasizing intelligent online services may nullify their sense of autonomy and in turn affect their acceptance intention. Enterprises have therefore focused on the best ways through which to provide intelligent online services. Based on the technology acceptance model, this study constructs a theoretical model of the impact of perceived control and power on adolescents’ acceptance intention of intelligent services. Through a scenario experiment involving an intelligent online recommendation service, 195 participants were obtained to test the model. The results show that the adolescents’ perceived control affects their acceptance intention of intelligent online services through their perceived usefulness. The adolescents’ sense of power moderates the influence of perceived control on perceived usefulness. This study supplements the research on intelligent online services and provides a reference for online merchants seeking to design such service processes.